2011
DOI: 10.1002/joc.2114
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the retrieval of cloud properties from radiation measurements over snow and ice

Abstract: ABSTRACT:We critically review and improve a simple method to extract year-round records of cloud optical thickness from radiation measurements made by automatic weather stations (AWSs) over snow and ice surfaces. A 'longwaveequivalent cloudiness', N ε , obtained from longwave radiation measurements, is combined with the effective cloud optical thickness, τ , from shortwave data, to obtain consistent, year-round information on cloud properties. The method is applied to radiation data from six AWSs in Dronning M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
0
36
1
Order By: Relevance
“…The cloud cover generated by WRF clearly exceeds the approximations based on the AWS measurements of LW↓ and air temperature following Kuipers Munneke et al (2011). In contrast with our findings, Aas et al (2015) reported underestimation of the cloud optical depth at Ny Ålesund (20 m a.s.l.)…”
Section: Discussioncontrasting
confidence: 91%
“…The cloud cover generated by WRF clearly exceeds the approximations based on the AWS measurements of LW↓ and air temperature following Kuipers Munneke et al (2011). In contrast with our findings, Aas et al (2015) reported underestimation of the cloud optical depth at Ny Ålesund (20 m a.s.l.)…”
Section: Discussioncontrasting
confidence: 91%
“…AWS measurements near Svea show a range of clear‐sky LW in of 100 to 200 W m − 2 as a function of air temperature, with an increase up to 300 W m − 2 due to cloud forcing [ Kuipers Munneke et al ., ]. A similar range was also found by Town et al .…”
Section: Resultsmentioning
confidence: 99%
“…The weakest winds are blowing from the NW and E at both stations. We computed cloud optical thickness using an algorithm that relates the observed SW ↓ to the theoretical clear-sky value of SW ↓ (Fitzpatrick et al, 2004), extrapolated to the winter months using a good correlation between cloud optical thickness and the longwave radiation balance in summer (Kuipers Munneke et al, 2010). The cloud cover at AWS 15 is generally optically thicker than at AWS 14 (Fig.…”
Section: Near-surface Meteorologymentioning
confidence: 99%